The Role of Classical Music Therapy on Dysmenorrhea Pain and Anxiety in Pelita Harapan University Medical Students - Godjali, Handriani Almira; Haryanto, Hori; Sungono, Veli (Medicinus, 2023)
Introduction: Dysmenorrhea is menstrual pain that often occurs in young women. The pain felt in every women can be different from one another. Anxiety experienced by each women can also worsen the menstrual pain. Efforts to treat dysmenorrhea can be in the form of non-pharmacological therapy, one of which is music therapy.Aim: This study uses an experimental method with random allocation to divide 122 respondents who are medical students of Pelita Harapan University into a control group and an intervention group.Methodology: The intervention group has been given anexperiment of random allocationin the form of classical music therapy for 20 minutes on the first day of the respondent getting menstruation. As for the control group given 40Hz sound for 20 minutes. The data analyzed using chi-square and wilcoxon test.Results: The results of the study found that the average menstrual pain in the control group before the intervention was 6.11 and after the intervention was 6.07. Meanwhile, in the intervention group, the average menstrual pain before being given classical music therapy was 6.46 and after the intervention was 3.39.Conclusion: So that classical music therapy is effective for reducing anxiety by 0.77 and the menstrual pain scale is 3.07 in the group given classical music therapy with P value <0.001.